Becoming bourgeois : love, kinship, and power in provincial France, 1670-1880 - Johnson, Christopher H. (Cornell University Press, 2015)
This book traces the fortunes of three French families in the municipality of Vannes, in Brittany - Galles, Jollivet, and Le Ridant - who rose to prominence in publishing, law, the military, public administration, and intellectual pursuits over the course of the eighteenth and nineteenth centuries. Revisiting complex issues of bourgeois class formation in France from the perspective of the interior lives of families, the book argues that the most durable and socially advantageous links forging bourgeois ascent were those of kinship.